HUBUNGAN POLA KONSUMSI VITAMIN C TERHADAP KADAR GLUKOSADARAH DAN TRIGLISERIDA PADA PASIEN DIABETES MELITUS RAWATJALAN DI RSUD Dr. MOEWARDI - Nurlita, Nurul, Elida Soviana, S.Gz., M.Gizi, Fitriana Mustikaningrum, S.Gz, M.Sc (2015)
Background: uncontrolled diabetes mellitus will to complication of various Complications like stroke, hypertension, and heart disease. Complications due to increased production of free radical for high blood glucose levels. To keep blood glucose levels to normal, it necessary good consuming vitamins c. Vitamin c is necessary for diabetics mellitus to prevent oxidative and blood glucose levels in lowering triglycerides. objective: to know patterns of consumption vitamin c and glucose levels of triglyceride in the blood as in diabetes mellitus. Method: this study was observational with of cross sectional approach. Data consumption patterns of vitamin c, used food frequency (FFQ laboratories to examination and blood glucose levels and triglycerides. data analysis used spearman rank test. Results: of: intake of vitamin c from food and supplements of vitamin c was enough (98.6 %), frequency of intake vitamin c was enough ( 97,2 %), 79,2 % sampled with high blood glucose levels and 62.5 % sample with normal levels of triglycerides .result of Spearman rank test , there was no relationship patterns of consumption vitamin c to glucose blood level and triglyceride of diabetes mellitus patients in Moewardi hospital Advice: for patients diabetes mellitus, it is hoped obedient increase of knowledge and motivation of food containing vitamin c to lower blood glucose levels and triglycerides. For installation of nutrition, expected to improve service and counseling for patients diabetes mellitus with optimal